Respuesta del arroz oriza sativa l. variedad iniap 14 a la aplicación de silicio y reguladores fisiológicos - Castillo Moreno, Edwin Roberth (2011)
The present investigation was carried out it in the New property Esperanza" located in the place Guayacanes belonging to the parish Sands of the canton Sands, county of The Gold and you beginning between May and August of the 2009. They thought about the following objectives: to determine answer of the rice (Oriza sativa l.) variety INIAP 14 to the silicon application and physiologic regulators; to evaluate the answer of the rice variety INIAP 14 to the application of different physiologic regulators and; to analyze the profitability of the different treatments in study. The used variety was the INIAP 14 to be the more sowed in the injerencia area dedicated to the production of this cultivation. The studied variables were: macollos number to the 30 and 60 DDS, height of the plant to the floración (cm), productive children's percentage, panícula number for blow, longitude of the panícula (cm), number of grains for espiguilla, percentage of full espiguillas, I weigh of the grain, yield in kg/ha, profitability of the treatments, problems fitosanitarios. The factors that were used were silicon (A) in dose of, 100 ml, 150 ml and 200 ml for each 100 liters of broth. And for the factor (B) the bioestimulantes oligosacáridos b1, for the regulator complex b2 and sour giberélico b3. A statistical design of blocks was used totally at random with factorial arrangement 4x4, for that which the statistical program MINITAB was used 15. You concluded that the silicon application in their biggest dose (200 ml/100 L), but bioestimulantes contributed positively to the yield of the plant. The effect of the silicon was not noticed in the percentage of full espiguilla while that for the biorreguladores the oligosacáridos marked positive difference. When carrying out the economic analysis, the treatments where oligosacáridos was applied in combination with silicon they were profitable in its bigger dose.